Exploring awareness of metacognitive knowledge and acquisition of vocabulary knowledge in primary grades: a latent growth curve modelling approach. Issue 4 (29th November 2022) - Teng, Mark Feng
Abstract: This study explores how primary school children develop their metacognitive knowledge and vocabulary knowledge and how both types of knowledge are dynamically correlated from 1st to 4th grade. The longitudinal sample included 426 first-grade students ( M = 6.6 years, SD = .51; 50.2% boys, 49.7% girls) from five public primary schools in China. A set of tests on metacognitive knowledge and vocabulary knowledge were administered four times over four years. The one-on-one-basis metacognitive knowledge test was based on students' explanations about cognitive activities; the vocabulary knowledge test focused on students' breadth and depth of vocabulary knowledge. Latent growth curve modelling was used to study developmental change. Results showed that participants' metacognitive knowledge and vocabulary knowledge improved from 1st to 4th grade but not in a cumulative fashion. Participants' level of metacognitive knowledge was strongly associated with their vocabulary knowledge throughout the selected school years. The development of vocabulary knowledge breadth lagged behind vocabulary knowledge depth during the study period. These findings shed light on primary school students' development of metacognitive knowledge and vocabulary knowledge.